Pengaruh Investasi terhadap Penyerapan Tenaga Kerja sebagai Upaya Meningkatkan Pertumbuhan Ekonomi - Arti, Laila Krisna; Setiawati, Ririt Iriani Sri (Jurnal Bisnis Indonesia, 2024)
The level of investment is an important factor in the absorption aspect labor. This research aims toanalyze how investment influences labor absorption in Indonesia and its relationship to economicdevelopment. The research method used is qualitative descriptive research with literature study. Theresult of the study shows that investment has a positive influence on energy absorption work andreduce the unemployment rate in Indonesia.investment can help expand a company’s operations thusleading to improvement productivity and employment. Government policy also plays a role indetermining the extent to which investment can influence labor absorption. Policies that supportinvestment such as tax incentives and adequate infrastructure will attract private investment. The roleof government is very important in a country by increasing the development of basic infrastructurewhich includes telecommunications, transportation, water supply which is the main contribution toefficient government spending to attract private sector investment. Government spending which canencourage private sector investment will create business opportunities which will later expand laborabsorption.Keywords: Investment; Labor; Economic Growth